Mildly Handicapped Students' Self-Awareness of Academic Skills - Miller, Maurice; Bommarito, Thomas ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Self awareness of academic skills by 9 primary age and 15 intermediate age mildly mentally handicapped (MiMH) students in a special class and 14 intermediate age learning disabled students in a resource room was measured. Ss completed a modification of H. Myklebust's Pupil Rating Scale. Results indicated primary MiMH Ss consistently rated themselves significantly more positively than they were rated by the teacher. Both intermediate MiMH and LD Ss rated themselves as more competent than teachers did, but there were more areas of correspondence between teachers' and students' ratings, particulary in the areas of spoken language, orientation, and behavior. It is suggested that MiMH and LD students might receive the most realistic feedback from teachers and parents in these skills areas. Complete versions of the teacher and student scales used in the study are appended. (CL)
ERIC Note: Paper presented at the Annual International Convention of The Council for Exceptional Children (61st, Detroit, MI, April 4-8, 1983).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Intermediate Grades; Learning Disabilities; Mild Disabilities; Mild Mental Retardation; Primary Education; Self Evaluation (Individuals); Speeches/Meeting Papers; Reports, Research